Cyprus as AI Saw it: Reinventing the Colonial Gaze (Exhibition UA) - Koutsomichalis, Marinos; Achilleos, Alexia (My University, 2021)
Digital prints of AI-generated text and images, British colonial-era books about Cyprus, mobile app. 'Cyprus as AI Saw it: Reinventing the Colonial Gaze' is part of 'Cyprus as AI Saw it', a wider artistic project thematic concerned with decolonial re-interpretations of the island's history. A hybrid AI system consisting of an AttnGAN text-to-image generation model and a RNN text generator, are trained with text from colonial handbooks of Cyprus, originally published when Cyprus was still part of the British Empire, as well as with a custom image dataset meant to reflect this colonial view of the island. This AI hybrid is then left to iterate, generating original colonial views of Cyprus upon demand. The resulting text and imagery are used in a number of related artistic outputs, exhibitions, events, and artifacts. Employing a variety of physical, digital, and hybrid media, audiences are encouraged to interact with the system, producing unique (and often individualised) colonial views of Cyprus. In this fashion, the project re-examines the historical relationship between coloniser and colonised, generating an alternative colonial narrative as a tactic to regain agency from a local point of view. In addition to some of the original colonial-era books which were used to train the decolonial AI system, the installation presents the outputs of the material generated by the AI system, in the form of a ‘decolonial’ book about the island of Cyprus. Visitors are encouraged to take a piece of decolonial text or image with them as a memento. The mobile app version of the project allows users to generate colonial text and image upon demand; it can be installed via the QR codes below (iOS/android):